Social health markers in the context of cognitive decline and dementia: an international qualitative study - Kristanti, Martina S.; Vernooij-Dassen, Myrra; Jeon, Yun-Hee; Verspoor, Eline; Samtani, Suraj; Ottoboni, Giovanni; Chattat, Rabih; Brodaty, Henry; Lenart-Bugla, Marta; Kowalski, Krzysztof; Rymaszewska, Joanna; Szczesniak, Dorota M.; et al. (Frontiers in Psychiatry, 2024)
Background Social health in the context of dementia has recently gained interest. The development of a social health conceptual framework at the individual and social environmental levels, has revealed a critical need for a further exploration of social health markers that can be used in the development of dementia interventions and social health measures. Objective To identify social health markers in the context of dementia. Method This international qualitative study included six countries: Australia, Germany, Indonesia, Italy, Poland, and the Netherlands. Using purposive sampling, three to five cases per country were recruited to the study, with each case consisting of a person living with dementia, a primary informal caregiver, an active network member, and a health care professional involved in the care of the person with dementia. In-depth interviews, using an agreed topic guide, and content analysis were conducted to identify known and new social health markers. The codes were then categorized against our conceptual framework of social health. Results Sixty-seven participants were interviewed. We identified various social health markers, ranging from those that are commonly used in epidemiological studies such as loneliness to novel markers of social health at the individual and the social environmental level. Examples of novel individual-level markers were efforts to live their life as usual and making own choices in, for example, keeping contact or refusing support. At a social environmental level, examples of novel markers were proximity (physical distance) and the function of the social network of helping the person maintaining dignity. Conclusions The current study identified both well-known and novel social health markers in the context of dementia, mapped to the social health framework we developed. Future research should focus on translating these markers into validated measures and on developing social health focused interventions for persons with dementia.